2021
DOI: 10.1080/22423982.2021.1943983
|View full text |Cite
|
Sign up to set email alerts
|

“Engaging stakeholders in integrating social determinants of health into electronic health records: a scoping review”

Abstract: Social, environmental, and behavioural factors impact human health. Integrating these social determinants of health (SDOH) into electronic health records (EHR) may improve individual and population health. But how these data are collected and their use in clinical settings remain unclear. We reviewed efforts to integrate SDOH into EHR in the U.S. and Canada, especially how this implementation serves Indigenous peoples. We followed an established scoping review process, performing iterative keyword searches in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…To realize these gains, institutional strategies need to be updated about what SDOH will be collected and via what structured fields/sections of the EHR [ 52 , 62 ]. Strategies must address workflow considerations such as collection upon patient registration (e.g., via MyChart or in person at kiosks and on tables in clinics), with or without assistance from navigators, and frequency (e.g., annually or more often) [ 29 , 30 , 72 ]. The AHC or PRAPARE frameworks [ 30 , 52 ] for structured EHR-based SDOH collection are key starting points for minimal, standardized collection, with additional questions added for some measures depending on local populations/needs [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To realize these gains, institutional strategies need to be updated about what SDOH will be collected and via what structured fields/sections of the EHR [ 52 , 62 ]. Strategies must address workflow considerations such as collection upon patient registration (e.g., via MyChart or in person at kiosks and on tables in clinics), with or without assistance from navigators, and frequency (e.g., annually or more often) [ 29 , 30 , 72 ]. The AHC or PRAPARE frameworks [ 30 , 52 ] for structured EHR-based SDOH collection are key starting points for minimal, standardized collection, with additional questions added for some measures depending on local populations/needs [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, when asked to consider how their community would view screening, concerns of patient privacy, stigmatization, shame [75], and need for trust with screening personnel arose [73][74][75] as did perceived risk of bias from providers. Patient answers suggested that screening needs to be conducted with empathy, and cultural and geographic sensitivity, especially with indigenous communities [72]. No small part of the necessary geographic sensitivity relates to the widely varying type and level of resources available in any given location.…”
Section: Evolving Context and Considerations For Ctsas And Other Heal...mentioning
confidence: 99%
“…This would also lead to better research on housing as a social determinant of health and a right and would increase the possibility of studying relationships between national homelessness counts and death in state level analyses. Future research might also further our understanding of the construction of social notes on housing and homelessness status in medical records through interviews with administrators and professionals in other settings (e.g., schools, law enforcement, medical centers) to better learn about constraints and opportunities for similar improvements to data within electronic health records (Cantor and Thorpe 2018; Wark et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, our results suggest that the relationship between having a Sámi identity, and the relevance of the Sámi identity when being in the patient-role is not clear. A recent scoping-review [ 26 ] argues that incorporating cultural identifiers into the electronic health record seems feasible, but careful considerations should be taken when registering sensitive non-health data. Article 9 in the Norwegian Personal Data Act prohibits the processing of information on ethnic, racial, religious, and philosophic convictions (among others) that can be linked to specific individuals.…”
Section: Discussionmentioning
confidence: 99%